2009
DOI: 10.1093/ndt/gfp454
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hypoxia-inducible factor attenuates renal injury in rat remnant kidney

Abstract: Activation of HIF by DMOG halted the progression of proteinuria and attenuated structural damage by preventing podocyte injury in the remnant kidney model. This renoprotection was accompanied by a reduction of oxidative stress, inflammation and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 47 publications
7
89
1
2
Order By: Relevance
“…This is consistent with the findings of a previous genetic study showing lower levels of ROS production and mitochondrial oxidative damage in muscle cells from PHD-deficient mice (47). In inflammatory bowel disease and chronic kidney failure, DMOG reduced secretion of proinflammatory cytokines, macrophage infiltration, and oxidative stress (48,49). Furthermore, in PHD2-haplodeficient mice, HIF-1 activity normalized blood vessel maturation and oxygen supply (50).…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the findings of a previous genetic study showing lower levels of ROS production and mitochondrial oxidative damage in muscle cells from PHD-deficient mice (47). In inflammatory bowel disease and chronic kidney failure, DMOG reduced secretion of proinflammatory cytokines, macrophage infiltration, and oxidative stress (48,49). Furthermore, in PHD2-haplodeficient mice, HIF-1 activity normalized blood vessel maturation and oxygen supply (50).…”
Section: Discussionsupporting
confidence: 89%
“…25 The finding that chronic HIF activation reduced proteinuria is in line with previous studies. Song et al 26 recently showed that HIF activation halted progression of proteinuria in a 27 reported that HIF activation by cobalt reduced renal expressions of TGF-b, connective tissue growth factor, and NADPH oxidase as well as reduced proteinuria, tubulointerstitial damage, and peritubular capillary loss in experimental type 2 diabetes. Indeed, tubulointerstitial fibrosis is a reliable marker for progression of kidney disease, and it is, therefore, interesting that HIF activation ameliorated fibrosis development in the diabetic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of HIF-stabilizing therapy have been found for a wide variety of ischemic disorders, such as myocardial and cerebral infarction or chronic kidney failure (48)(49)(50). An important focus of future research will be to specify the therapeutic targets of nonspecific pan-PHD inhibitors like DMOG to develop more specific, targeted drugs.…”
Section: Discussionmentioning
confidence: 99%